2020
DOI: 10.1093/qje/qjz039
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating a Better Future: How Interpersonal Skills Facilitate Intergenerational Investment*

Abstract: Using a randomized controlled trial, we study whether a negotiation skills training can improve girls’ educational outcomes in a low-resource environment. We find that a negotiation training given to eighth-grade Zambian girls significantly improved educational outcomes over the next three years, and these effects did not fade out. To better understand mechanisms, we estimate the effects of two alternative treatments. Negotiation had much stronger effects than an informational treatment, which had no effect. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 61 publications
2
42
0
2
Order By: Relevance
“…This research is in line with the theory put forward by Ashraf et al, (2020) which states that increasing the number of business units will increase the amount of output produced so that employment will increase and will reduce unemployment. This is in line with research conducted by Azoulay et al, (2019) and Tri (2004) which states that in relation to labor absorption it is influenced by the number of business units.…”
Section: The Effect Of the Number Of Business Units On The Employment Of Medium And Large Industrial Sectors In South Sulawesisupporting
confidence: 84%
“…This research is in line with the theory put forward by Ashraf et al, (2020) which states that increasing the number of business units will increase the amount of output produced so that employment will increase and will reduce unemployment. This is in line with research conducted by Azoulay et al, (2019) and Tri (2004) which states that in relation to labor absorption it is influenced by the number of business units.…”
Section: The Effect Of the Number Of Business Units On The Employment Of Medium And Large Industrial Sectors In South Sulawesisupporting
confidence: 84%
“…It was supported by emerging research on the benefits of non-cognitive or soft skills trainings. Teaching soft skills such as self-worth, interpersonal communication, and sense of control have been shown to promote a range of positive life outcomes, including improved productivity, earnings, health, and educational outcomes (Acevedo et al, 2017;Adhvaryu, Kala, and Nyshadham, 2018;Blattman, Jamison, and Sheridan, 2017;Ashraf et al, 2020;Heckman, Stixrud, and Urzua, 2006). Several studies have found soft skills trainings to be as or more effective in boosting employment and entrepreneurial outcomes compared to hard skills or technical trainings Barrera-Osorio, Kugler, and Silliman, 2020).…”
Section: Life Skills Trainingmentioning
confidence: 99%
“…Third, we pay close attention to the role of gender attitudes in cognitive and noncognitive aspects of skill accumulation. Recent experimental papers focus on identifying interventions that improve negotiation skills among adolescent girls in Zambia (Ashraf et al, 2020), promote gender attitudes among adolescents in Haryana (Dhar et al, 2018), and promote agency among adolescent girls in Rajasthan (Edmonds et al, 2019). The extent to which improvements in gender attitudes will translate to real economic gains for females in part depends on the role of gender attitudes in improving cognitive and noncognitive skills in low-and middle-income countries.…”
Section: Introductionmentioning
confidence: 99%